2018
DOI: 10.1177/1359105318816509
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the emotional experiences of young women with chronic pain: The potential role of self-compassion

Abstract: Chronic pain is multidimensional and includes an emotional dimension in addition to the physical and cognitive dimensions. Self-compassion, being touched by and open to one’s own suffering, has been identified as a useful resource during difficult experiences. The purpose of this narrative inquiry was to explore the role of self-compassion in the emotional experiences of women with chronic pain. Seven women participated in focus groups, reflective photo voice and one-on-one interviews. Three collective narrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 29 publications
1
13
0
1
Order By: Relevance
“…Consistent with the growing body of research focusing on self-compassion and health behaviors (Barnes et al, 2018;Carson et al, 2005;Sirois et al, 2015), our first hypothesis was partially supported. This study found a strong positive correlation between self-kindness, common humanity, and mindfulness, the three positive components of self-compassion, and all six domains of healthpromoting behaviors.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Consistent with the growing body of research focusing on self-compassion and health behaviors (Barnes et al, 2018;Carson et al, 2005;Sirois et al, 2015), our first hypothesis was partially supported. This study found a strong positive correlation between self-kindness, common humanity, and mindfulness, the three positive components of self-compassion, and all six domains of healthpromoting behaviors.…”
Section: Discussionsupporting
confidence: 79%
“…Germer, 2009;Neff, 2009;Neff and Beretvas, 2013;Yarnell and Neff, 2013;Zhang et al, 2019) as well as a variety of physical health and wellness outcomes. Selfcompassion was found to be related to decreased levels of pain, anger, tension, and emotional pain among individuals with chronic pain (Barnes et al, 2018;Carson et al, 2005). Selfcompassionate exercises were related to the lower levels of both emotional and physical symptoms of depression among a college student sample (Wong and Mak, 2016) as well as increased medical adherence among patients with cancer, chronic fatigue syndrome, fibromyalgia (Sirois and Hirsch, 2018), HIV (Brion et al, 2014), and celiac disease (Dowd and Jung, 2017).…”
mentioning
confidence: 97%
“…ally, women may also experience unique types of pain, such as menstrual pain, childbirth, and breastfeeding. Moreover, women's heightened susceptibility to emotional factors may exacerbate or trigger chronic pain compared to men [31,32]. Despite the evident prevalence of pain among the elderly community, there has been insufficient focus on the diagnosis and treatment of pain [9], leading to its frequent neglect or delayed management.…”
Section: Discussionmentioning
confidence: 99%
“…Several nurse researchers have conducted Clandinin and Connelly’s (2000) form of narrative inquiry to generate knowledge pertaining to people’s experiences of identity ( Caine, 2007 ; dela Cruz, 2014 ; Dewart et al, 2021 ; Estefan et al, 2019 ; Smith et al, 2018 ). As the affective emotional aspect of chronic pain is highly personal ( Barnes et al, 2018 ; Smith & Sparkes, 2009 ), narrative inquiry is a valuable methodology to understand the complex experience of living with chronic pain. By understanding how participants make sense of their experiences through stories, how chronic pain has shaped, and continues to shape, the identity of emerging adult women can be understood.…”
Section: Discussion: Narrative Inquiry and Contributions To Nursing K...mentioning
confidence: 99%